무릎관절 통증 환자에서 멀리건 관절가동술과 맥켄지 운동이 통증과, 균형, 관절가동범위에 미치는 영향 - 이호종; 김진영; 신영일 (대한정형도수물리치료학회지, 2022)
Background: This study aimed to compare the effects of the Mulligan mobilization with movement and McKenzie exercise after applying conservative physical therapy to patients with knee pain. Methods: Patients were randomly allocatied into two groups: the Mulligan mobilization with movement (10 subjects) and the McKenzie technique (10 subjects). Each group was givenr conservative physical therapy and manual therapy sessions, three times week, for four weeks. The pain intensity was measured using the visual analogue scale (VAS). The cervical range of motion (ROM) was measured with a goniometer. Balance was measured using the modified Berg balance scale (BBS). Results: After four weeks of therapy, VAS (p<.05) decreased significantly, and ROM and balance increased siginficantly in both groups(p<.05). There was a significant improvement in knee extension (p<.05) in the McKenzie group compared to the Mulligan group. No intergroup differences were found with respect to the knee flex, VAS, and BBS (p>.05). Conclusion: The McKenzie exercises are more effective than Mulligan mobilization with movement for improving knee extension. Both interventions have the same effects on pain relief, in increasing knee flexion ROM and improving balance in patients with knee pain.